Spectroscopic Studies as a Toolbox for Biophysical and Chemical Characterization of Lipid-Based Nanotherapeutics - Fernandes, Eduarda; Soares, Telma B.; Gonçalves, Hugo; Lúcio, Marlene (Frontiers in Chemistry, 2018)
The goal of this study is to provide tools to minimize trial-and-error in the development of novel lipid-based nanotherapeutics, in favor of a rational design process. For this purpose, we present case-study examples of biophysical assays that help addressing issues of lipid-based nanotherapeutics’ profiling and assist in the design of lipid nanocarriers for therapeutic usage. The assays presented are rooted in spectroscopic methods (steady-state and time-resolved fluorescence; UV-Vis derivative spectroscopy; fluorescence anisotropy and fluorescence lifetime image microscopy) and allow accessing physical-chemical interactions between drugs and lipid nanocarriers, as well as studying interactions between lipid-based nanotherapeutics and membranes and/or proteins, as this is a key factor in predicting their therapeutic and off target effects. Derivative spectroscopy revealed Naproxen’s high distribution (LogD ≈ 3) in different lipid-based nanocarriers (micelles and unilamellar or multilamellar vesicles) confirming the adequacy of such systems for encapsulating this anti-inflammatory drug. Fluorescence quenching studies revealed that the anti-inflammatory drugs Acemetacin and Indomethacin can reach an inner location at the lipid nanocarrier while being anchored with its carboxylic moiety at the polar headgroup. The least observed quenching effect suggested that Tolmetin is probably located at the polar headgroup region of the lipid nanocarriers and this superficial location may translate in a fast drug release from the nanocarriers. Fluorescent anisotropy measurements indicated that the drugs deeply buried within the lipid nanocarrier where the ones that had a greater fluidizing effect which can also translate in a faster drug release. The drug binding strength to serum albumin was also compared for a free drug (Clonixin) or for the same drug after encapsulation in a lipid nanocarrier DSPC:DODAP (2:1). Under both conditions there is a strong binding to serum albumin, at one binding site, suggesting the need to produce a stealth nanosystem. Finally the cellular uptake of lipid nanocarriers loaded with Daunorubicin was investigated in cancer cells using fluorescence lifetime imaging microscopy. From the images obtained it was possible to conclude that even at short incubation times (15 min) there was a distribution of the drug in the cytoplasm, whereas for longer incubation periods (4 h) the drug has reached the nucleus.